Takhrij al Furu Alal Usul Periode Ijtihad Sahabat dan Tabiin dalam Persfektif Sosiologi dan Antropologi Hukum - Erwan (International Journal of Publication Unit (IUJP) Agus Salim Metro, 2022)
Some see the other laws as a thing of the past. Some people see that it will still exist until now. However, others argue that it still exists but in the development of the times it is getting eroded and more technical. Islam as a treatise brought by Muhammad SAW is considered a pure, harmonious, cheerful and sublime message. Islam and the concept in its application is quite simple, and in its application through ibrah through the earliest creatures. The character of the prophet kanjeng gives security and mercy to the universe. Law is not just a normative conception, because if the law only contains normative, juridical or positivistic normative it will only cause the loss of substantive value in law or legal norms. The study of legal anthropology provides a new perspective and as an alternative solution in understanding the law. The period of companions and tabiin is a period of development of interpretation and takmil (explanation and refinement). Companions and tabi'in are models of mujtahids in Islamic treasures. This can be seen in the legal treasures with determination through ijtihad which refers to the values ​​and studies of sociology and legal anthropology.